Evaluation of coeliac trunk and hepatic artery variations in thoracic CT angiography in patients with congenital heart disease - Kemal Bugra Memis; Hasan Bulut; Hasibe Gokce Cinar; Berna Ucan; Cigdem Uner; Ozkan Kaya; Sonay Aydin (Elsevier, 2024)
Introduction: Understanding the variations of abdominal vascular structures is important for preventing complications of abdominal surgical procedures for gastrointestinal disease such as necrotizing enterocolitis or others that may arise in patients with congenital cardiac disease. We analysed the coeliac trunk and its branches in children with congenital heart disease to determine whether there is a greater prevalence of associated vascular abnormalities. Methods: We retrospectively analysed thoracic computed tomography (CT) angiograms performed in our hospital in paediatric patients with congenital heart disease. We documented the anatomical variations observed in abdominal sections in which the coeliac trunk and hepatic arteries were included in the field of view. We used the Uflacker classification to describe anatomical variants of the coeliac trunk, and the Michels classification and its modified version (Hiatt classification) to describe the anatomy of the hepatic artery system. Results: Our study included 178 patients with congenital heart disease. We identified coeliac trunk variants in 10.7% of the patients. Gastrosplenic trunk was to the most prevalent variant, amounting to 5.6% of total cases. We found hepatic artery variations in 19.1% of the patients. According to the Michels classification, the prevalence of accessory left hepatic artery arising from the left gastric artery as 4.5%, compared to 6.7% based on the Hiatt classification. Conclusion: The prevalence of coeliac trunk and hepatic artery variations in patients with congenital heart disease was not greater in our study compared to other series in the literature. Clinicians must be vigilant about the variations detected in multislice CT scans to avoid complications resulting from vascular abnormalities, especially in patients who undergo abdominal surgery. Resumen: Introducción: Comprender las variaciones de las estructuras vasculares abdominales es importante para prevenir complicaciones de procedimientos quirúrgicos abdominales por enfermedades gastrointestinales, como la enterocolitis necrotizante u otras que pueden desarrollarse en pacientes con cardiopatías congénitas. Se examinará el tronco celíaco y sus ramas en niños con cardiopatía congénita para determinar si hay una mayor prevalencia de anomalías concomitantes. Métodos: Exploración retrospectiva de pacientes pediátricos con cardiopatías congénitas sometidos a una angiotomografía computarizada (angio-TC) en nuestro hospital. Se registraron las variaciones anatómicas en secciones abdominales en las que el plano de adquisición incluía el tronco celíaco y las arterias hepáticas. Se utilizó el método de Uflacker para describir las variantes anatómicas del tronco celíaco. Las variaciones en el sistema de la arteria hepática se caracterizaron mediante la clasificación de Michels y la versión modificada de Hiatt. Resultados: La muestra incluyó a 178 pacientes pediátricos con cardiopatías congénitas. Se encontraron variaciones de la arteria celíaca en el 10,7% de los pacientes. La variante más prevalente era el tronco gastroesplénico, que representaba el 5,6% de todos los casos. La prevalencia de variaciones de la arteria hepática fue del 19,1%. La prevalencia observada de arteria hepática izquierda accesoria con origen en la arteria gástrica izquierda fue del 4,5%, según la clasificación de Michels y del 6,7% según la clasificación de Hiatt. Conclusión: En nuestro estudio, no se observó una prevalencia mayor de variaciones del tronco celíaco y de la arteria hepática en pacientes con cardiopatías congénitas en comparación con lo descrito en series previas. Los médicos deben prestar atención a las variaciones detectadas en las tomografías computarizadas multicorte para evitar complicaciones derivadas de variaciones vasculares, especialmente en pacientes sometidos a cirugía abdominal.